Curved microstructures promote osteogenesis of mesenchymal stem cells via the RhoA/ROCK pathway. (August 2017) - Zhang, Qi; Lin, Shiyu; Zhang, Tao; Tian, Taoran; Ma, Quanquan; Xie, Xueping; Xue, Changyue; Lin, Yunfeng; Zhu, Bofeng; Cai, Xiaoxiao
Abstract: Objectives: Cells in the osteon reside in a curved space, accordingly, the curvature of the microenvironment is an important geometric feature in bone formation. However, it is not clear how curved microstructures affect cellular behaviour in bone tissue. Materials and methods: Rat primary bone marrow mesenchymal stem cells (BMSCs) on wavy microgrooves were exposed to PDMS substrates with various curvatures to investigate alterations in cellular morphology and osteogenic differentiation. Additionally, the expression levels of RhoA and its effectors were examined by immunofluorescence and quantitative PCR to determine the mechanisms of curvature‐dependent osteogenic differentiation. Results: Wavy microgrooves caused dramatic nuclear distortion and cytoskeletal remodelling. We detected a noticeable increase in the expression of osteogenic‐related genes in BMSCs in wavy microgroove groups, and the maximum expression was observed in the high curvature group. Moreover, immunofluorescent staining and quantitative RT‐PCR results for RhoA and its effectors showed that the RhoA/ROCK signalling pathway is associated with curvature‐dependent osteogenic differentiation. Conclusions: Our results illustrated that curved microstructures could promote BMSC differentiation to the osteogenic lineage, and the osteogenic effects of higher curvature are more obvious. Wavy microstructures could also influence the RhoA/ROCK pathway. Accordingly, curved microstructures may be useful in bone tissue engineering.